2021
DOI: 10.1038/s41598-021-93546-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of dysautonomia in long COVID-19 patients

Abstract: Increasing numbers of COVID-19 patients, continue to experience symptoms months after recovering from mild cases of COVID-19. Amongst these symptoms, several are related to neurological manifestations, including fatigue, anosmia, hypogeusia, headaches and hypoxia. However, the involvement of the autonomic nervous system, expressed by a dysautonomia, which can aggregate all these neurological symptoms has not been prominently reported. Here, we hypothesize that dysautonomia, could occur in secondary COVID-19 in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
155
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(184 citation statements)
references
References 45 publications
3
155
0
3
Order By: Relevance
“…Postural orthostatic tachycardia and other manifestations of dysautonomia have frequently been described among patients post-COVID-19 [39 , 40] . Here, we showed that at 2-3 months, heart rate recovery on CPET, an indirect measure of autonomic health, was impaired in patients compared to controls [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Postural orthostatic tachycardia and other manifestations of dysautonomia have frequently been described among patients post-COVID-19 [39 , 40] . Here, we showed that at 2-3 months, heart rate recovery on CPET, an indirect measure of autonomic health, was impaired in patients compared to controls [41] .…”
Section: Discussionmentioning
confidence: 99%
“…One of the causes of PCS has been hypothesised as ‘dysautonomia’, It has been shown that participants with PCS and fatigue had dysregulation of heart rate variability ( 20 ). The authors stated that such dysautonomia could lead to fatigue and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the sometimes fatal respiratory syndrome, COVID-19 leads to multi-visceral complications associated with inappropriate immune and inflammatory response [ 2 ], endothelial dysfunction and thromboembolic disorders [ 3 ]. Damage to the central and peripheral nervous system [ 4 , 5 ] was reported, including the autonomous nervous system that showed dysregulation at the early [ 6 ] and late phases of the disease [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%